Respuesta :
[tex] = \tt \frac{2}{3} (6x - \frac{1}{6} ) + 3x [/tex]
[tex] =\tt \frac{2}{3} \times 6x - \frac{2}{3} \times \frac{1}{6} + 3x[/tex]
[tex] =\tt \frac{2 \times 6}{3}x - \frac{2 \times 1}{3 \times 6} + 3x[/tex]
[tex] = \tt \frac{12}{3} x - \frac{2}{18} + 3x [/tex]
[tex] =\tt 4x - \frac{2 \div 2}{18 \div 2} + 3x[/tex]
[tex] = \tt4 x- \frac{1}{9} + 3x[/tex]
[tex] = \tt4x + 3x - \frac{1}{9} [/tex]
[tex] \color{plum}= \tt\bold{7x - \frac{1}{9} }[/tex]
Therefore,
[tex] \color{hotpink}\tt \frac{2}{3} (6x - \frac{1}{6} ) + 3x \color{plm}= \color{plum}\tt\bold{7x - \frac{1}{9} } [/tex]